Comprehensive review of DNA gyrase as enzymatic target for drug discovery and development - K. Rajakumari; K. Aravind; M. Balamugundhan; Manjunathan Jagadeesan; Ambiga Somasundaram; Parthiban Brindha Devi; Pasiyappazham Ramasamy (Elsevier, 2024)
DNA gyrase is a member of the DNA topoisomerase protein family that catalyzes the conversion of different topological forms of DNA into one another. It is the sole enzyme that causes DNA to negatively supercoil. The enzyme is tetrameric with two GyrA ("A'') and two GyrB ("B'') subunits. DNA gyrase is an ideal target for medication because of its basic properties in bacterial cells and the lack of gyrase activity in eukaryotes. Antibacterial medications, including quinolones and derivatives based on coumarins that specifically target DNA gyrase, underscore the significance of the enzyme in the fight against bacterial infections. In addition to the typical antibiotic-binding sites, including novobiocin and fluoroquinolones, several other areas are being used in drug discovery. Simocyclinone, thiophene, gepotidacin, halogen atoms in the para position of the phenyl right-hand side (RHS) moiety, and coupled cell division B (CcdB) are examples of novel bacterial type II topoisomerase inhibitors (NBTIs). These binding sites are structurally and chemically active and inhibit the supercoiling activity of topoisomerase. This article provides an overview of DNA gyrase inhibition using synthetic and natural precursors aimed at medication development and discovery.